The role of the library café as a learning space: A comparative analysis of three universities. (September 2019) - Deng, Qi; Allard, Bradley; Lo, Patrick; Chiu, Dickson K.W.; See-To, Eric W.K.; Bao, Alex Z.R.
Although food and drink have traditionally been prohibited in libraries, in recent years, there have been increased joint ventures between libraries and coffee shops like Starbucks. Although library cafés are perceived mostly for social networking and recreational purposes, an increasing number of students are conducting both their formal and informal learning at the library cafés, instead of inside the physical libraries. Using a quantitative comparative approach, this study also aims to identify the similarities and differences in the usage of library cafés amongst students at three different universities in Asia and the United States – namely, the University of Tsukuba, located in Japan, the University of Hong Kong, and the University of Kentucky in the USA. Furthermore, this study explores the educational, social, and recreational roles that library cafés play in the students' college experience and daily lives. Online questionnaire surveys were used to gauge library patrons' usage and perceptions of both the library and café spaces, as well as their preferences for formal and informal learning and recreation. From the 314 responses collected from all three universities, the results indicated that a majority of the respondents considered the library café as an important part of their campus life, though a majority of them would still prefer formal learning within the library building, and certain recreational activities outside the library café. Besides, the library café also functions like a multi-functional hub where everyone can find their own use, ranging from being a place for learning to a place for socialization purposes.